2016
DOI: 10.3389/fpsyg.2016.00562
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Processing and Attention Control Impairments in Children with Anxiety: An Integrative Review of Event-Related Potentials Findings

Abstract: Anxiety disorders in adults have been associated with biased processing of emotional information which may be due to a deficit in attentional control. This deficit leads to an hypervigilance and a selective attention toward threatening information. Event-related potentials (ERPs) have been used to study this topic in anxious adults. Similar biases have been reported in children with anxiety but researches investigating the ERPs components underpinning these biases are more scarce. However, the understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 136 publications
(239 reference statements)
1
13
0
Order By: Relevance
“…Indeed, some recent studies have confirmed the importance of individual difference in ERP signals related to social comparison ( Hu et al. , 2017 ; Wang et al. , 2017 ; Qi et al.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, some recent studies have confirmed the importance of individual difference in ERP signals related to social comparison ( Hu et al. , 2017 ; Wang et al. , 2017 ; Qi et al.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, differences between ERN and correct-response negativity amplitude in 7-year-old children predicted SAD symptoms at age 9 (Lahat, Lamm, et al, 2014). It should be noted however that the ERN is not specific to SAD, but also found in other anxiety disorders in children (Wauthia & Rossignol, 2016). The CRN and Pe are each studied in only one developmental study and were not related to social anxiety (Lahat, Lamm, et al, 2014;McDermott et al, 2009).…”
Section: Developmental Considerationsmentioning
confidence: 99%
“…It should be noted that, both P3 and LPP refer to large and slow positive potentials, which peak at the parietal electrodes later than 300 ms post-stimulus. In this study, the term “P3” is used to refer to the relatively earlier positive component (about 300 ms) with a sharper peak, and the term “LPP” to refer to the slower positive wave (after 500 ms) with a blunter peak 41 , 42 . In addition to the three ERP components that have been often mentioned in the DF paradigm, the present study investigated early components such as the occipital P1 and the frontal P2, which are well-known attention-related components 43 , 44 , but have not been explored in previous DF studies.…”
Section: Introductionmentioning
confidence: 99%